Role of monocytes and endothelial cells in heparin-induced thrombocytopenia - Madeeva, Daria; Cines, Douglas B.; Poncz, Mortimer; Rauova, Lubica (Thrombosis and Haemostasis, 2016)
Heparin-induced thrombocytopenia (HIT) is an autoimmune disorder characterised by thrombocytopenia and thrombosis. The mechanisms leading to platelet destruction are complex and the thrombotic complications of HIT appear to be due to multiple different intravascular targets. The dual binding of HIT antibodies to platelet surface PF4/GAG complexes and to FcγRIIA likely leads to both platelet clearance and to their direct activation. Monocytes and endothelial cells bind PF4 with higher avidity than platelets and are more resistant to competitive removal of surface-bound PF4 in the presence of heparin. Binding of HIT antibodies to PF4/glycosaminoglycan complexes on the surface on these cells leads to their activation and increased procoagulant activity. Binding of higher levels of PF4 released from activated platelets to the endothelium may lead to changes of the anticoagulant properties of the glycocalyx and target the endothelial cells for HIT antibodies. Pathogenic antibodies bound to endothelial cells further promote prothrombotic conditions by a mechanism that is independent of FcγR activation, yet not completely understood. A more detailed understanding of the role of monocytes and endothelium may identify new targets for intervention to mitigate the risk of thrombosis with less impact on systemic haemostasis than current approaches to treatment for this serious disorder.
Keywords: Thrombosis; coated platelets; FcγRIIA; glycosaminoglycans; PF4